When (and How) Is Theory of Mind Useful? Evidence from Life-Span Research - Francesca Baglio (Frontiers Research Topics, 2017)
Theory of Mind (ToM) or mentalization is the ability to understand and foresee the behavior referring to one's own and others' mental states (Premack & Woodruff, 1978; Wimmer & Perner, 1983). This capacity, which is considered the most representative mechanism of social cognition, is a multifaceted set of competences liable to influence - and be influenced by - a manifold of psychosocial aspects. Studies on typical and atypical/clinical development during life showed that ToM is frequently delayed (e.g. in deafness) or impaired in many clinical conditions (e.g. Autism Spectrum Disorder, Attention Deficit Hyperactivity Disorder, Schizophrenia, Borderline Personality Disorder, Parkinson's Disease, Alzheimer's Disease) and, on the other hand, may not be unequivocally a positive experience. It is therefore possible to consider the existence of multiple kinds of Theory of Mind. In fact, ToM may vary along a quantitative and a qualitative continuum. As for the quantitative dimension, the continuum is constituted by the fluctuation between high and low levels of ToM ability in different clinical conditions. Along this continuum, impairment can mean "not enough" ToM (for example in Autism Spectrum Disorder) as well as "too much" ToM (for example in Schizophrenia and Borderline Personality Disorder). The qualitative dimension - highly interrelated with the quantitative one - regards the shift between adaptive (e.g. prosocial, nice ToM) vs. unadaptive (e.g. antisocial, nasty ToM) mental states content. The issue is discussed in light of recent evidence from outstanding researchers working on typical and atypical/clinical populations along the life-span. Findings from the fields of psychology, neuropsychology and neuroscience enrich the research topic argumentation.